G105(P) Ethnic differences in cultural and spiritual perceptions, and coping strategies in families with epilepsy. (27th April 2016) - Joshi, A; Stevens, E
Abstract : Aims: To determine factors emerging from the cultural and spiritual background of different ethnic groups, which could influence perception and management of epilepsy in children. Methods: A retrospective questionnaire based survey, in families whose children have epilepsy. Data collected when families attended epilepsy clinics at Luton and Dunstable University Hospital, UK and when visited by the Epilepsy Specialist Nurse in the community. We extracted data on ethnic origin, religion/spiritual belief, concepts of epilepsy, stigmatisation, degree of influence of religion and cultural beliefs and use of non-medical therapies. We compared Caucasian and Asian families. The data was analysed using Fisher's exact test and Chi-square test with Yates correction. Results: A total of 70 families participated in the survey. 28 were of Caucasian, 30 of Asian, 6 of African and 6 of mixed ethnic origin. There were 34 Muslims, 29 Christians, 6 Atheist and 1 unspecified. Significantly more Asian families believed that epilepsy was influenced by non-medical causes- e.g. fate or destiny (50%), or spirit related (43%) than Caucasian families (none). There was no difference in perception of stigmatisation between Caucasian and Asian families. Influence on treatment and management of epilepsy by family, religion or culture was significantly more common in Asian compared to Caucasian families (p < 0.001). Non-medical therapies (use of traditional healers, prayers, complementary therapies) were used in significantly more Asian compared to Caucasian families (p < 0.001). Conclusions: Non-medical influences on perception of cause and on treatment of epilepsy were more common in Asian compared to Caucasian families, but non-medical therapy did occur in Caucasian families. Since the UK has a diverse population, consisting of a wide range of spiritual and cultural beliefs, the NHS should strive to understand all viewpoints, allowing for a more holistic healthcare provision, and possible improvement in patient outcome.